Politisi dengan tingkat elektabilitas rendah dan strategi branding politik: analisis multimodalitas akun instagram puan maharani - Gendis Ayu Putri Ning Yudhi Hatmanti; Nyarwi Ahmad (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Politicians potentially nominated by political party as a candidate for running in the elections commonly expected to get endorsement from a substantial number of electoral markets. Only few of them have a chance to do so however. In consideration of this, most of these politicians select and use particular semiotics codes strategically as an element to establish political branding strategy they carry out through media platforms, including social media. Having adopted Aaker’s (1997) concept of brand personality, this article examines how did Puan Maharani exploit semiotic code resources communicated through his Instagram account (@puanmaharaniri) as a political branding strategy. 3 materials posted in his Instagram account with high level engagement were selected, extracted and analyzed using multimodal analysis. The findings are follows. Puan deployed various kinds of semiotic code resources strategically. This includes strategic selection of represented participants, gestures, image composition, clothing colors, and hair styling. She kept exploiting all dimensions of brand personality, as posited by Aaker (1997), but she highlighted following three dimensions of this brand personality, which are competence, sophistication, and ruggedness much more and did it consistently. Political branding strategy she carried out was directed to create her personal political image as a populist politician; though this image belongs to her toughest rival from the party she associated with, which is Ganjar Pranowo